Mechanism and Management of Fentanyl-Induced Cough - Chen, Rong; Tang, Ling-hua; Sun, Tao; Zeng, Zi; Zhang, Yun-yan; Ding, Ke; Meng, Qing-tao (Frontiers in Pharmacology, 2020)
Fentanyl-induced cough (FIC) often occurs after intravenous bolus administration of fentanyl analogs during induction of general anesthesia and analgesia procedure. The cough is generally benign, but sometimes it causes undesirable side effects, including elevated intra-abdominal, intracranial or intraocular pressure. Therefore, understanding the related mechanisms and influencing factors are of great significance to prevent and treat the cough. This paper reviews the molecular mechanism, influencing factors and preventive administration of FIC, focusing on the efficacy and side effects of various drugs in inhibiting FIC to provide some medical reference for anesthesiologists.